A GENERALIZATION OF THE STRONGLY CESARO ´ IDEAL CONVERGENCE THROUGH DOUBLE SEQUENCE SPACES (2020)
In this paper, some algebraic properties of Ces´aro double ideal convergent sequence spaces are defined and proved. Those spaces are defined as C I nm and C I 0nm. Furthermore, this paper shows some inclusion relations on these spaces which are established and proved.